Deoxyspergualin in relapsing and refractory Wegener's granulomatosis. Issue 7 (19th August 2008) - Flossmann, O; Baslund, B; Bruchfeld, A; Cohen Tervaert, J W; Hall, C; Heinzel, P; Hellmich, B; Luqmani, R A; Nemoto, K; Tesar, V; Jayne, D R W
Abstract : Objectives: Conventional therapy of Wegener's granulomatosis with cyclophosphamide and corticosteroids is limited by incomplete remissions and a high relapse rate. The efficacy and safety of an alternative immunosuppressive drug, deoxyspergualin, was evaluated in patients with relapsing or refractory disease. Methods: A prospective, international, multicentre, single-limb, open-label study. Entry required active Wegener's granulomatosis with a Birmingham vasculitis activity score (BVAS) ⩾4 and previous therapy with cyclophosphamide or methotrexate. Immunosuppressive drugs were withdrawn at entry and prednisolone doses adjusted according to clinical status. Deoxyspergualin, 0.5 mg/kg per day, was self-administered by subcutaneous injection in six cycles of 21 days with a 7-day washout between cycles. Cycles were stopped early for white blood count less than 4000 cells/mm 3 . The primary endpoint was complete remission (BVAS 0 for at least 2 months) or partial remission (BVAS <50% of entry score). After the sixth cycle azathioprine was commenced and follow-up continued for 6 months. Results: 42/44 patients (95%) achieved at least partial remission and 20/44 (45%) achieved complete remission. BVAS fell from 12 (4–25), median (range) at baseline to 2 (0–14) at the end of the study (p<0.001). Prednisolone doses were reduced from 20 to 8 mg/day (p<0.001). Relapses occurred in 18 (43%) patients after a median of 170 (44–316) days after achieving remission. Severe or life-threatening (⩾ grade 3) treatment-related adverse events occurred in 24 (53%) patients mostly due to leucopaenias. Conclusions: Deoxyspergualin achieved a high rate of disease remission and permitted prednisolone reduction in refractory or relapsing Wegener's granulomatosis. Adverse events were common but rarely led to treatment discontinuation.